PENATALAKSANAAN FISIOTERAPI PADA KONDISI POST FRAKTUR COLLES 1/3 DISTAL DEKSTRA dengan MODALITAS INFRARED dan TERAPI LATIHAN - Fitrocha ,; Eko Budi Prasetyo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Colles' fracture is  a fracture due to trauma that occurs in the wrist where the fracture is shaped  like  a  spoon,  caused  by  the  patient  fell  and  rested  on  one  hand  stretched  in  the open  and  pronation,  and  their  body  into  the  rotating  arm  (endorotasi).  Problems  on postoperative Colles' fracture is often the case, namely: pain, limitation of LGS, atrophy, decreased  functional  ability.  To  provide  effective  and  efficient  handling,  then  was examined for pain, limitation of LGS, muscle strength, atrophy and functional ability. In addressing  these  issues  is  given  in  the  form  Infrred  modalities  and  exercise  therapy. Having given over 6  times the action  can be obtained  significant  results, namely: silent pain  1.5cm  to  be  0cm,  tender  5.5cm  to  2.6cm,  motion  pain  8.5cm  to  5.4cm,  LGS  on elbow:  R=30°-0°-15°  to  R=65°-0°-45°,  wrist:  S=30°-0°-30°  to  S=45°-0°-55°,  F=5°-0°- 20° to F=15°-0°-25°, MCP I: S=0°-0°-30° to the S=0°-0°-55°, MCP II-V: S=0°-0°-35° to S=20°-0°-70°, MMT on the flexor-extensor elbow: 3 to 4, pronator - elbow supinator: 2 to 3, flexor - extensor wrist: 1 to 3, radial - ulnar deviator wrist: 2 to 4, MCP flexor I: 2 to 4,  extensor  MCP  I:  3  to  4,  flexor  MCP  II-V:  2  to  4,  and  extensor  MCP  II-V:  3  to  4, Antopometri  the  atrophy  remains  Proc.  Styloideus  ulna  17cm,  5cm  to  19cm  distal, proximal  to  the  13.5  cm  5cm,  17cm  and  10cm  proximal  to,  and  functional  ability  in Duruoz Hand Index from 56 to 30. Keywords: Colles Fracture, pain, LGS, MMT, antopometri, Duruoz Hand Index.